2016
DOI: 10.1038/nmicrobiol.2016.147
|View full text |Cite
|
Sign up to set email alerts
|

The essential mycobacterial amidotransferase GatCAB is a modulator of specific translational fidelity

Abstract: Although regulation of translation fidelity is an essential process, diverse organisms and organelles have differing requirements of translational accuracy, and errors in gene translation serve an adaptive function under certain conditions. Therefore, optimal levels of fidelity may vary according to context. Most bacteria utilize a two-step pathway for the specific synthesis of aminoacylated glutamine and/or asparagine tRNAs, involving the glutamine amidotransferase GatCAB, but it had not been appreciated that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
184
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(188 citation statements)
references
References 49 publications
4
184
0
Order By: Relevance
“…This was in question because DD Mtb generation proceeded most quickly when RIF was used at a concentration (100 μM) far above its minimal bactericidal concentration for replicating bacteria (0.01-0.08 μM) (20,21). The need for high concentrations of RIF may reflect impaired uptake of RIF by starved Mtb (21) or could be related to the phenotypic RIF resistance attributed to stress-induced protein mistranslation (39). Regardless, the RIF dose requirement did not reflect selection for heritable RIF resistance.…”
Section: Discussionmentioning
confidence: 99%
“…This was in question because DD Mtb generation proceeded most quickly when RIF was used at a concentration (100 μM) far above its minimal bactericidal concentration for replicating bacteria (0.01-0.08 μM) (20,21). The need for high concentrations of RIF may reflect impaired uptake of RIF by starved Mtb (21) or could be related to the phenotypic RIF resistance attributed to stress-induced protein mistranslation (39). Regardless, the RIF dose requirement did not reflect selection for heritable RIF resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Mtb H37Rv (Rv) and a locally isolated, fully drugsusceptible clinical isolate [strain 165 (40)] were used in the experiments as described. For the latter, drug sensitivity to first-line antibiotics was verified according to standard diagnostic laboratory procedures and strain-verified as Beijing type by multiplex PCR of the RD105 region as previously described (41).…”
Section: Methodsmentioning
confidence: 99%
“…Javid and colleagues found that mistranslation of two amino acids, glutamate for glutamine, and aspartate for asparagine, resulted in modified RNA polymerase (RpoB, encoded by rv0667 ) that was more resistant to rifampicin (85). Only a minority of cells in a wild type population accumulated enough mutant copies of RpoB with Asp in place of Asn at position 434 to survive rifampin at its MIC (85, 86). When these cells were expanded, the MIC remained the same.…”
Section: Class I Persisters: Rare Drug Tolerant Cellsmentioning
confidence: 99%
“…When these cells were expanded, the MIC remained the same. Analogous to the situation with hip genes in E. coli , mutation in the GatCAB aminotransferase that normally corrects mistranslation of the Asn codon increased the frequency of these class I phenotypically tolerant mycobacteria, but the MIC was no greater in progeny of these cells than in the population from which they were selected (86). Rendering M. smegmatis nonreplicating by acidic pH or nutrient starvation led to protein mistranslation and phenotypic kanamycin resistance (85).…”
Section: Class I Persisters: Rare Drug Tolerant Cellsmentioning
confidence: 99%